37. HEALTH STATUS OF FIRST-YEAR STUDENTS AT VIETNAM NATIONAL UNIVERSITY ENROLLING IN 2021-2022 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the health status of first-year students at Vietnam National University, Hanoi, academic year 2021-2022.Subject and methods: Cross-sectional descriptive study on 1,829 first-year students of Vietnam National University, Hanoi admitted and had an entrance health check at Hospital of Vietnam National University, Hanoi.Results: The rate of students with chronic energy deficiency was 27.7%; the rate of overweight and obesity was 6.66%. The average systolic blood pressure was 114.54 ± 10.72 mmHg, the average diastolic blood pressure was 71.79 ± 7.21 mmHg. The rate of anxiety according to the Spielberger scale was 30.07%. Disease status: eye diseases (79.12%), dental and maxillofacial diseases (17.35%); ear, nose and throat (8.39%); motor system diseases (4.93%); hypertension (3.74%); dermatological diseases (3.19%) and gastroduodenal syndrome (2.63%). The rate of health reaching very good and good is quite high, reaching 86.73%; the health reaching average is 11.1%.Conclusions: The health status of first-year students of Vietnam National University, Hanoi in the 2021-2022 school year still has some problems related to obesity, anxiety and some common diseases. The school, family and students need to coordinate to take care of and improve the health of students regularly.
Keywords: Students; health check-up